2021
DOI: 10.1051/e3sconf/202126302030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of pumps of irrigation pumping stations

Abstract: The article presents the results of a study of the wear of individual pump elements, a decrease in their efficiency and significant losses. The nonidentical operation of the extreme and middle pumps was established. The uneven approach of water to the extreme units created reverse flows of water in the suction pipes, work with vibrations of modes close to cavitation. The modernization of the pumps improved the cavitation characteristics due to the elimination of the cavitation center at the impeller inlet in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Based on software drawings, the continuous movement of the flow in the pump was analyzed. Field studies and diagnostic results showed the need for a connection between theoretical and experimental studies [12,13]. Based on surveys and research conducted in the production company, it was determined that the influence of reading forces on the working parts of the pumps was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Based on software drawings, the continuous movement of the flow in the pump was analyzed. Field studies and diagnostic results showed the need for a connection between theoretical and experimental studies [12,13]. Based on surveys and research conducted in the production company, it was determined that the influence of reading forces on the working parts of the pumps was determined.…”
Section: Methodsmentioning
confidence: 99%
“…One of the principles of water management is to ensure development and management to solve the problems associated with using limited water resources, increase the efficiency of their use, and impact sustainable development. One of the ways to improve the efficiency of water use and operation of the MWLS is to reduce unproductive losses, mainly hydraulic ones [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…IOP Publishing doi:10.1088/1755-1315/1142/1/012004 2 In the system of the Ministry of Water Resources of the Republic of Uzbekistan, there are more than 20 systems of machine water lifting for irrigation, which provide water resources for more than 2.1 million hectares of irrigated lands of the Republic [2]. For their normal functioning, channels with hydraulic structures, pumping stations with power equipment are operated [3,4].…”
Section: Introductionmentioning
confidence: 99%